Oil-From-Water Removal Under Low Gradient Magnetic Separation (LGMS) - Runnizam, Muhaimin Hazmi Khai (Universiti Sains Malaysia, 2022)
A magnetic Pickering emulsion (MPE) was synergistically stabilized by the iron oxide nanoparticles (IONPs) coated by poly(sodium 4-styrenesulfonate) (PSS) and poly(diallyldimethylammonium chloride) (PDDA) as well as the adjacent PDDA molecules. MPE, IONP, IONP-PSS, and IONP-PSS-PDDA were synthesised. Their chemical, physical, and magnetic characteristics were analysed in depth. Under macroscopic motion of MPE, the synthesised MPE was examined. A smartphone camera captured the fluctuating turbidity of the MPE suspension. ImageJ was used to analyse all photos. The MPE magnetic separation efficiency reached 80% in 30 minutes on a macroscopic scale under all conditions. However, the MPE colloidal stability was lowest at pH 10 compared to pH 3 and DI water under a flocculation time of 2 hours. MPE at pH 10 needed the least time to achieve the greatest separation efficiency. As a result, MPE at pH 10 exhibited cooperative magnetophoresis, as it irreversibly flocculated during magnetophoresis. During the macroscopic study, the MPE did not deform or coalesce under the magnetic field B of 0.02 T ~ 0.64 T and magnetic field gradient (dB/dz), ∇B of 25.09 T/m ~ 94.57 T/m. Magnetophoresis study demonstrated that IONP-composites on emulsion droplets corresponded with significant positive MPE zeta potential. This is because, in addition to IONP-PSS-PDDA, PDDA molecules occupied considerable portions of emulsion droplet surfaces. Magnetophoresis of newly synthesised MPE improved oil recovery prospects.